HAFIZUN INFLUENCE ON AL-KASBU IN ISLAMIC BANKS IN EAST KALIMANTAN PROVINCE - Wati, Maria (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This article aims to analyze in depth the influence of the concept of Hafizun on al-Kasbu in Islamic banks in East Kalimantan Province. This study uses quantitative and qualitative approaches that are useful for explaining the existence and role of a research object or research variable on other research variables descriptively, by analyzing the causal relationship between research variables statistically. The results of the study indicate that Hafizun, which is the motivation of employees at Islamic banks in East Kalimantan Province, consisting of benefits, luck, seeking wealth through worship, working with the heart, seeking Allah's pleasure, peace of mind, living for the hereafter, and toyiban, has a significant positive influence on al-Kasbu. As Hafizun increases, al-Kasbu also increases, with Hafizun always feeling emotionally connected to the Islamic Bank, ultimately creating strong al-Kasbu at the Islamic Bank in East Kalimantan Province. This is evidenced by the increasing values of all Hafizun indicators, where the graphical trend has been rising over the past five years, from 2008 to 2012. Hafizun has a significant positive influence on al-Kasbu, and the better/higher the level of Hafizun, the better/higher the level of al-Kasbu. This study rejects Blancard and Abraham Maslow's theory of leadership and work motivation, which emphasizes indicators such as: praise, material rewards, wages, and worldly well-being. However, in terms of intuitive analysis, employees of Islamic banks in East Kalimantan Province perceive well-being as both material and spiritual, with indicators of motivation and faith in worldly life ultimately leading to happiness in the afterlife. Most employees are happy because they are grateful for the dynamic process of Allah's destiny that continues to unfold. The integrated conclusion of this study is that Hafizun has a significant positive influence on al-Kasbu.